Boosting the energy renovation rate of the private building stock in Italy: Policies and innovative GIS-based tools. (October 2017) - Caputo, Paola; Pasetti, Giulia
Highlights: European and Italian building stock are old and with low energy performance. Local energy planning is fundamental to renovate the building stock. Different barriers and drivers affect private and public buildings owners. Policies and measures to stimulate energy retrofit of private buildings are presented. Abstract: In Europe and Italy, the building stock is a great consumer of energy and there is the need to renovate it. The local administration is best placed to develop local energy plans to lead the change toward a more energy efficiency built environment. A wide research aimed to individuate main barriers and drivers to energy-oriented buildings retrofit at urban level has been developed. The first part focuses on the public administration, while the work here presented focuses on private stakeholders, since the private buildings represent the majority of the building stock. We conducted an analysis of the barriers and drivers that influence the energy renovation by private stakeholders (building owners, building manager and citizens, companies) and proposed a framework of policies, a municipal energy model and innovative Geographic Information System (GIS)-based tools. We adopted a hybrid approach, using both real and statistical data. Moreover, we integrated already existing databases linking information instead of starting anew. We developed the tools for a medium-sized municipality in northern Italy, implementing methods and procedures that can be applied for any Italian municipality. The tools are flexible and customizable and their capability could be enriched by better data availability (i.e. real energy consumption data).